A PSYCHOLOGICAL APPROACH TO ENHANCING ADOLESCENT ROAD SAFETY: INTEGRATING BEHAVIORAL THEORY AND DRIVING SIMULATION - Audinda Virsa Leinia; Mochamad Firmansyah Sofianto; Erina Rahmadyanti; Ninik Wahju Hidajati (Jurnal Abdi Masyarakat, 2026)
This community service is a preventive program to address the serious issue of road accidents, which significantly affect young drivers in countries like Indonesia. Recognizing that human behavior is the main cause, a community program was launched for 36 high-risk, 17-year-old male students at SMK Negeri 7 Surabaya. The program used a dual approach: theoretical lessons based on the Theory of Planned Behavior and practical training with a driving simulator. This method aimed to improve their knowledge and skills, as well as their attitudes and confidence about safe driving. The results were a significant success. Before the program, students had low scores for their attitudes towards safe driving, social influence, and confidence in their skills. However, after the intervention, scores for all three areas improved dramatically. The most impressive gain was in self-confidence, which jumped from 28% to 72%. Post-program feedback also showed that the students found the lessons easy to understand and the driving simulator highly realistic and helpful. These findings prove that this combined approach is a very effective way to educate young drivers, providing a strong model that can be used to reduce accidents and save lives.